Islam dan Multikulturalisme: Urgensi, Transformasi, dan Implementasi dalam Pendidikan Formal - Yani , Muhammad Turhan; Suyanto , Totok; Ridlwan, Ahmad Ajib; Febrianto , Nur Fitroh (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2020)
The current development of society demonstrates openness in evaluating various aspects of life, including understanding towards religious matter. In another side, this fact turns into a challenge because some people, especially some Muslims, are still exclusive. Responding to the challenge, Islam as a set of universal principle should operate in providing solutions through its views upon the essence of multiculturalism. This paper examines theoretically the factual reality of multiculturalism in Indonesia, how Islam positions multiculturalism, and views for educational institutions in developing multiculturalism perspectives to grow inclusive attitudes in society. The results of the study show that the multiculturalism facts in Indonesia cannot be neglegted and must be maintained and developed by promoting tolerance and justice. In Islamic perspectives, multiculturalism is a fact that is often found in the al-Qur’an and Hadith as well as in the historical records of the Prophet’s life. Through educational channels, the perspective of multiculturalism can be disseminated to develop a society that respects the value and practice of the multiculturalism itself.